Advanced training in anaesthesia - Prout, Jeremy; Jones, Tanya; Martin, Daniel ([Oxford] : Oxford University Press, 2014)
Ideal for trainees taking the Final FRCA, this curriculum-based guide contains everything candidates need to know to pass this final major hurdle in anaesthetic training, though the knowledge within the book will continue to apply beyond training.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 8, 2014).
Keywords: Anesthesiology